Analysis of Inefficiency in Management Systems (Case Study: Rayani Air) - Siti Nurbalqis Binti Md Hassan; Daisy Mui Hung Kee; Nur Sarah Solehah Binti Mohamed Elias; Wan Nor Shafinaz Binti Wan Shafie; Shahira Binti Ahmad Shukri; Danah AlAjmi (International Journal of Tourism and Hospitality in Asia Pasific, 2019)
Air transportation have become one of the fastest growing industries because of the economic deregulation. This situation makes airlines company started to think out of the box to create an exciting business strategy in order compete in the market. The aim of this study is to investigate the inefficiency of Rayani Air’s management system. Rayani airline is an airlines services that operated in Malaysia. It is the fourth airline in the world that has made it mandatory that each of the Muslim cabin crew be sharia compliant. Unfortunately, there are negative comments about their inefficiency of the systems by customers. Through observation and analysis of existing branding design, this study attempts to develop a new strategy for improving Rayani Air’s management system. In this case, improvement in this system is necessary for restoring consumers’ trust and convincing stakeholders to invest in the company. We conclude that rebranding for failure organization is a crucial task and should be given the highest priority.